Hubungan Konsumsi Makanan Kariogenik dengan Kejadian Karies Gigi dan Status Gizi Anak Tk Pembina Mojosongo Surakarta - Arista, Eka, Susi Dyah Puspowati, S.P, M.Si, Muwakidah, S.KM, M.Kes (2016)
Introduction : Dental caries is one of the dental and oral health proble,s frequently encountered society, which among groups of children under five. Consuming excess cariogenic foods may increase the risk of dental caries. Children who experience dental caries in a long period of time will influence nutrient intake and nutrition status. The prevalence of dental caries by 58,1% children TK Pembina Mojosongo Surakarta in 2015. Research Purpose : To determine the relationship cariogenic food intake with the incidence of dental caries and nutritional status of children Tk pembina mojosongo Surakarta Research Method : The design of this study was obsevation method with crosssectional approach and the subject were 30 chosen by random sampling from A-KB grade students that fulfill the inclution criteria. Data of Cariogenic food were obtained using food frequencies. The caries level was measured by indeks caries. The nutritional status level was measured by antropometri. Results : The results showed that Children consumption most of the cariogenic foods(70%) having dental caries(66%). Most of children (80%) having normal nutritional status. The results of chi square, there were relationship between the cariogenic consumption foods with dental caries (p:0,001), there was no a relationship between the cariogenic consumptions with nutritional status (p:0,232) Conclusions : there were relationship between the cariogenic consumption foods with dental caries, there was no a relationship between the cariogenic consumptions with nutritional status